1 Colonial laws of New York from the Year 1664 to the Revolution 49-50 (1894) - (:unkn) unknown (My University, 1665)
"Besides the Generall stock of each Town Every Male within this Government from Sixteen to Sixty years of age, or not freed by public Allowance, shall if freeholders at their own , if sons or Servants at their Parents and Masters Charge and Cost, be furnished from time to time and so Continue well furnished with Armes and other Suitable provition hereafter mentioned: under the penalty of five Shillings for the least default therein Namely a good Serviceable Gun, allowed Sufficient by his Military Officer to be kept in Constant fitness for present Service, with a good sword bandeleers or horne or worme a Scowerer a priming wire Shott Badge and Charger one pound of good powder, four pounds of Pistol bullets or twenty four bullets fitted to the gunne , four fathom of Serviceable Match for match lock gunn four good flints fitted for a fire lock gunn..."
Keywords: REQUIRED POSSESSION